2020
DOI: 10.4317/medoral.23374
|View full text |Cite
|
Sign up to set email alerts
|

Quality of information about oral cancer in Brazilian Portuguese available on Google, Youtube, and Instagram

Abstract: Background: To evaluate the quality of oral cancer information in Brazilian Portuguese on Google, YouTube, and Instagram. Material and Methods: The first 100 links of each platform characterized the initial sample. The websites and Instagram were evaluated using the JAMA benchmarks, the Discern instrument, and the Flesch readability index (Flesch Reading Ease). The existence of Health on the Net (HON) code was also registered on websites. The usefulness of each video on YouTube was classified as not useful, sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
27
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 25 publications
(37 reference statements)
4
27
0
12
Order By: Relevance
“…Our study identified most videos as moderately useful, because they mentioned the clinical characteristics of the disease and provided information about treatment and prognosis. Despite methodological differences, this was also found in a study by Passos et al, 19 in which most of the Table 3. Analyses of usefulness and quality assessment score in relation to length in minutes, views, viewer's interaction, and reliability score.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our study identified most videos as moderately useful, because they mentioned the clinical characteristics of the disease and provided information about treatment and prognosis. Despite methodological differences, this was also found in a study by Passos et al, 19 in which most of the Table 3. Analyses of usefulness and quality assessment score in relation to length in minutes, views, viewer's interaction, and reliability score.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have analyzed YouTube TM as a source of information on different pathological processes that can affect oral health. [11][12][13][18][19][20] Our study is the first to examine the content of YouTube TM videos on OLP and to evaluate the quality of the information provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this time of confinement due to COVID-19, it seems to us that it may be a good opportunity to draw the attention of dentists outside their offices, to the main clinical features of oral SCC, its current epidemiological trends, stressing the association between early diagnosis and good prognosis. However, recently we have evidenced that the information on oral SCC available on the internet is of low quality, both on websites, YouTube and Instagram [3,4]. Thus, members of international and national Professional Associations (Oral Pathology and Medicine, Oral and Maxillofacial Surgery, Head and Neck Surgery and Otorhinolaryngology), and Dental and Medical Schools around the world, could mobilize themselves to produce quality online content on Websites, Instagram, YouTube, and other apps that allow the transmission of videos and lives.…”
mentioning
confidence: 99%
“…Individual specialists are also encouraged for such action. It is noteworthy that quality online content must have several criteria that ensure readability, confidence, and usefulness [4].…”
mentioning
confidence: 99%